Alzheimer's Disease Including Focal Presentations - Villain, Nicolas; Dubois, Bruno (Seminars in Neurology, 2019)
Alzheimer's disease (AD) is the commonest neurodegenerative disease and the most frequent cause of dementia. It affects 30 million people worldwide. Current research criteria focus on biomarkers' status for amyloid and tau using positron emission tomography and cerebrospinal fluid analysis, independent of clinical status. Current epidemiological data, which mostly rely on biomarker-undetermined AD cases, have highlighted ApoE4 and age as the main risk factors. Rare autosomal dominant mutations also account for a small fraction of early-onset AD. The main clinical phenotype at presentation is the amnestic phenotype targeting episodic memory. This is followed by rarer phenotypes such as posterior cortical atrophy, logopenic variant of primary progressive aphasia, frontal variant AD, corticobasal syndrome, and other even rarer presentations mimicking language variants of frontotemporal dementia. Main differential diagnoses include hippocampal sclerosis with TDP-43, primary age-related tauopathy, argyrophilic grain disease, frontotemporal lobar degeneration, Lewy body disease, chronic traumatic encephalopathy as well as nondegenerative disorders such as cerebrovascular disease, chronic alcohol consumption, limbic encephalitis, medial temporal lobe epilepsy, and others. Co-occurrence of AD pathology with other neurodegenerative and vascular diseases is common and increases with age. This presents a challenge in current clinical practice due to a lack of reliable biomarkers for non-AD neurodegenerative diseases.
Keywords: Alzheimer's disease; diagnosis; CSF; epidemiology; dementia